2005
DOI: 10.1007/s10067-005-1117-6
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis and heart abnormalities: do cardiac conduction disorders, valve regurgitation and diastolic dysfunction occur more often in male patients with diagnosed ankylosing spondylitis for over 15 years than in the normal population?

Abstract: The objective of this study was to determine the rate of selected cardiac pathologies (conduction disorders, valve regurgitation and diastolic dysfunction) in patients with long-standing ankylosing spondylitis (AS) and compare the results with the prevalence in the normal population. A rheumatologic (structured questionnaire interview) and cardiac evaluation (resting electrocardiography and echocardiography) was performed in 100 male subjects with AS and a disease duration of more than 15 years. The rates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 30 publications
(30 reference statements)
3
48
0
9
Order By: Relevance
“…Kinsella et al 9 reported a mean duration of AS of 21 years; the Brunner group reported a mean duration of 33 years. 10 Confi rming previous fi ndings, Dik et al found no second/third degree atrioventricular block after up to 11 years of follow-up. 11 This group defi ned as "early" an AS with diagnosis duration of less than two years.…”
Section: Discussionmentioning
confidence: 63%
“…Kinsella et al 9 reported a mean duration of AS of 21 years; the Brunner group reported a mean duration of 33 years. 10 Confi rming previous fi ndings, Dik et al found no second/third degree atrioventricular block after up to 11 years of follow-up. 11 This group defi ned as "early" an AS with diagnosis duration of less than two years.…”
Section: Discussionmentioning
confidence: 63%
“…Abnormal increased activity has been shown in AS patients both in our study and previous studies. [29][30][31][32] It is predicted that these patients may have high risk for the development of AF. Though there is still no clear evidence, we believe that increased incidence of AF in AS patients may be related to chronic inflammation and increased myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Inflammatory rheumatic diseases trigger cardiovascular conditions, increasing mortality and morbidity. 19 The risk of atherosclerosis, in which inflammation plays a primary role, was increased in AS patients.…”
Section: Discussionmentioning
confidence: 99%